Study on Calculation Method of Soluble Aerosol Removal Efficiency Under High Humidity Condition - Li, Yingzhi; Ma, Qianchao; Sun, Zhongning; Gu, Haifeng; Zhou, Yanmin; Shi, Kaiyi (Frontiers in Energy Research, 2019)
Pool scrubbing is a potential method to remove aerosol particles under accident conditions of nuclear power plants. The relative humidity of aerosol laden gas will increase significantly when passing through the water pool, which will most likely induce hygroscopic growth of soluble aerosol. The hygroscopic growth of soluble aerosol can lead to the deviation of the size distribution of aerosol at the outlet of the water pool, resulting in a large evaluation error of the removal efficiency. In order to solve this problem, the size distributions of sodium chloride at the upstream and downstream of bubble column were measured at a gas flow rate of 4 lpm and a liquid height of 80 cm, respectively. Two methods of calculating aerosol actual size-dependency removal efficiency were proposed and compared. One method is directly calculating the removal efficiency by adding a diffusion drying tube installed at the upstream of Scanning Mobility Particle Sizer (SMPS) to reduce the relative humidity of sample gas below the efflorescence point. Another method is modifying the aerosol size distribution and concentration curve by using the hygroscopic growth theory of soluble aerosols. The experiment results obtained by the two methods are in good agreement.